1993
DOI: 10.1017/s002185960008552x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed advancement and sowing date on establishment, bolting and yield of sugarbeet

Abstract: An advancing and devernalizing treatment for sugarbeet seed has been developed which, in England, allows sowing to be brought forward safely by c. 10 days to around 10 March. Experiments done each year from 1988 to 1991 were used to assess the value of this change. They showed that sugar yield increased by 0-048 t/ha/day because seed advancement resulted in more rapid emergence, and by 0042 t/ha/day as a result of earlier sowing. As an average of all appropriate data from experiments in England since the 1950s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…Sowing date strongly affects yields: our model predicts that each week's advance in sowing into low‐AWC soils during March and April will result in sugar yield gains of 0.2–0.3 t ha −1 (Figure 7a). These values are similar to yield changes measured in field experiments (Durrant et al. , 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Sowing date strongly affects yields: our model predicts that each week's advance in sowing into low‐AWC soils during March and April will result in sugar yield gains of 0.2–0.3 t ha −1 (Figure 7a). These values are similar to yield changes measured in field experiments (Durrant et al. , 1993).…”
Section: Discussionsupporting
confidence: 87%
“…As for the improvement in the yield of sugar beet by priming, Durrant et al (1993) calculated a 0.048 t ha-1 d-1 increase in yield by the promotion of emergence in Great Britain. Heyes et al (1997) reported a 1.8% increase in yield in 1995 and a 1.…”
Section: Optimum Water Content Of Seeds During Primingmentioning
confidence: 99%
“…Sugar beet is generally grown in a four-or five-course rotation in conjunction with cereals, potatoes, oilseed rape or set-aside/industrial break crops (Jaggard, Limb & Proctor 1995). The sugar beet crop is sown after the first week in March, and preferably before May (Durrant, Marsh & Jaggard 1993). Recommended sowing densities correspond to around 11 plants m ', with a 20 cm plant spacing and 55 cm row spacing.…”
Section: Album and The Sugar Beet Rotationmentioning
confidence: 99%